Intertwinement of stress response regulons in Bifidobacterium breve UCC2003 - Zomer, Aldert (Landes Bioscience, 2010)
Bifidobacteria constitute an important component of the microbiota of the gastrointestinal tract of humans and other mammals. Various bifidobacterial strains are commercially exploited because of their perceived beneficial role in the maintenance of gut homeostasis. We have determined the response of B. breve UCC2003, a Gram-positive bacterium originally isolated from the nursling stool of a breast-fed infant, to several stresses (heat, osmotic, solvent) using transcriptomics, classical techniques and in silico analysis, as well as the transcriptional response of B. breve UCC2003 to oxidative stresses caused by the exposure to diamide, peroxide and environmental oxygen. Integration of these results allowed the formulation of a model for an interacting regulatory network for stress response in B. breve UCC2003, where HspR controls SOS response and the ClgR regulon, which in turn regulates and is regulated by HrcA. This model of an interacting regulatory network is believed to represent the paradigm for stress adaptation in bifidobacteria.